Anogenital Mammary-Like Glands: A Study of Their Normal Histology With Emphasis on Glandular Depth, Presence of Columnar Epithelial Cells, and Distribution of Elastic Fibers. (September 2017) - Konstantinova, Anastasia M.; Kyrpychova, Liubov; Belousova, Irena E.; Spagnolo, Dominic V.; Kacerovska, Denisa; Michal, Michal; Kerl, Katrin; Kazakov, Dmitry V.
Abstract : Abstract: The normal histology of anogenital mammary-like glands (AGMLG) has been studied previously, but some aspects, including glandular depth, presence of columnar epithelium resembling columnar cell change/hyperplasia as defined in mammary pathology, and distribution of elastic fibers, have not been previously investigated. To address these issues, we studied 148 AGMLG identified in 133 paraffin blocks sampled from 64 vulvar wide excision or vulvectomy specimens (64 patients, various indications for surgery). The depth of AGMLG ranged from 0.64 to 3.9 mm. Epithelial columnar cell change was noted in 33.1% of all AGMLG, whereas columnar cell hyperplasia was detected in 10.1%. Occasionally, combinations of cuboidal epithelium and columnar cell change were seen within 1 histological section. Of 22 specimens stained for elastic fibers, in only 6 (27.3%) cases were elastic fibers found around glands. Periductal elastic fibers were demonstrated around 3 of the only 5 ducts, which were available for analysis in slides stained for elastic fibers. The depth of AGMLG should be taken into account when planning topical and surgical therapies for lesions derived or evolving from AGMLG. Alterations identical to columnar cell change may represent a normal variation of AGMLG.